By substitution
Repalce the value of x in first equation:
4.4 y + 4y = 6
8.4y = 6
y = 6/8.4 = 1/1.4
Multiply both numeratoy and denomenator by 5 to get the answer 5/7
y = 5/7
To find x:
Replace y as 5/7 in the first equaton:
x + 4y = 6
x + (4 x 5/7) = 6
x = 6 - 20/7
x = 42/7 - 20/7 = 22/7
x = 22/7; y = 5/7.
Solve the following system of equations
x + 4y=6
x= 4-4y
A. The solution is an ordered pair ( , )
B. No Solution
2 answers
sub x = 4 - 4y into the first
4 - 4y + 4y = 6
4 = 6
contradiction, therefore we have no solution
4 - 4y + 4y = 6
4 = 6
contradiction, therefore we have no solution